A Case of Small Intestinal Myoepithelial Hamartoma - Sasaguchi, Masatoshi; Motojima, Teiji; Nagamachi, Yukio; Yamada, Syuji; Shinoda, Yasuo (Nippon Shokaki Geka Gakkai zasshi, 1998)
A case of myoepithelial hamartoma of the small intestine, which is particularly rare among benign tumors of the small intestine, was observed. The patient was a 70-year-old man. He was examined in this hospital with the chief complaint of upper abdominal pain. On CT of the abdominal region, targer-shaped thickening of the small intestine was observed from the upper left to the lateral region of the abdomen, and the illness was diagnosed as intussusception. The symptom was not alleviated by palliative therapy, nd progress of intussusception was observed in reexamination by CT. He was diagnosed as having intussusception caused by a tumor in the small intestine and received a laparotomy. A 40-cm intussusception of the jejunum at 80-cm from the ligament of Treitz was found. After manual repositioning, a tumor 4.0×2.5×2.5cm in size was palpated in the front portion of the intussusception. A 15-cm length of the jejunum including the tumor was resected. In the histological study, growth of smooth muscle and mixed ductal proliferation were found in the internal circular muscle layer, and the illness was diagnosed as myoepithelial hamartoma. The course after the operation was good, and he was discharged on the 21 st day of hospitalization.